Adaptive Learning Management of the Merdeka Curriculum in an Islamic Boarding School - Syidrah Syidrah; Andi Sukmawati Assaad; Bustanul Iman RN (Universitas Cokroaminoto Palopo, 2026)
The urgency of this study lies in aligning the flexibility of Kurikulum Merdeka with the unique system of Islamic boarding schools to create an adaptive and value-based learning model. The implementation of the Merdeka Curriculum in Islamic boarding school contexts presents unique managerial and pedagogical challenges due to the need to integrate national education standards with pesantren traditions. However, limited studies have examined how learning management is operationalized within this dual-structure system. This study aims to analyze the learning management practices in implementing the Merdeka Curriculum at a pesantren-based junior secondary school. This research employed a qualitative case study design. The participants consisted of the school principal, curriculum coordinator, subject teachers, and tahfidz teacher who were directly involved in curriculum implementation. Data were collected through semi-structured interview guides, classroom observation sheets, and document analysis checklists covering teaching modules, assessment records, and institutional policy documents. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. Triangulation across interviews, observations, and documentation was conducted to ensure credibility and consistency of findings. The findings indicate that curriculum implementation reflects an adaptive learning management model characterized by integrated planning, student-centered and project-based instruction, differentiated learning strategies, and holistic assessment practices. The study highlights how pesantren institutions reinterpret national curriculum reform contextually while maintaining institutional identity, although challenges related to teacher readiness and resource limitations remain evident.